Experiences of meaningful occupation among diverse populations – A qualitative meta-ethnography - Christel Leufstadius; Lisbeth Nilsson; Pia Hovbrandt (Scandinavian Journal of Occupational Therapy)
Background Few studies synthesising knowledge about meaningful occupation are available. Meta-ethnography allows the synthesising of a variety of empirical findings and translational knowledge may be developed.Aim Investigate how individuals from diverse cultures and contexts experience meaningful occupation as described in qualitative research, applying meta-ethnographic approach.Material and methods The study was based on 44 qualitative articles, selected by following a systematic procedure. Articles published between 2003-2021 were included. Studies on children, intervention and review articles were excluded. All authors conducted the analysis and synthesis, in several steps, and reached a consensus interpretation of the data.Results Five categories explaining why and how people experienced meaning emerged. They were represented in all contextual settings. The main category was 1) Constructing identity and self-actualising throughout life. The other four categories were 2) Cultivating valued feelings 3) Spiritualising by being energised or disentangled 4) Connecting and belonging 5) Rhythmizing and stabilising by being occupied.Conclusion and significance The synthesis provided novel insights into how people experience meaning in occupation in various contexts as part of their process of constructing identity and self-actualisation throughout life. This knowledge is valuable as expanding and nuancing the understanding of meaningful occupation.